Cutaneous Melanoma with Brain Metastasis: Report of 193 Patients with New Observations. - Alenka Gugger; Raymond L Barnhill; Burkhardt Seifert; Silvia Dehler; Holger Moch; Claire Lugassy; Ewerton Marques-Maggio; Elisabeth J Rushing; Daniela Mihic-Probst (PLoS ONE)
Background Brain metastasis is a common endpoint in patients suffering from malignant melanoma. However, little is known about factors that predispose to brain metastases. Objective We performed a retrospective clinical and pathological investigation of melanoma patients with brain metastases in order to better characterise this patient population. Methods 193 melanoma patients with brain metastasis histologically diagnosed between 1990 and 2015 at the University Hospital Zurich were retrospectively identified and further specified for sex, age at diagnosis and detection of brain metastasis, and localisation. In addition, data were extracted regarding the subtype of primary melanoma, Breslow tumour thickness, Clark Level, mutation status, extent of metastatic spread and history of a second melanoma. Results We found a significant male predominance (n = 126/193; 65%; p < 0.001). Breslow tumour thickness showed a wide range from 0.2 to 12.0 mm (n = 99; median 2.3 mm). 14 of 101 melanomas (14%) were classified as T1, thereof 11 (79%) were found in men. In 32 of 193 patients (17%), the primary melanoma was unknown. Conclusions Of special interest in our series is the high incidence of male predominance (79%) in cases of thin metastasing melanoma (14%), implicating genetic or epigenetic (hormonal) gender differences underlying tumour progression. Additionally, the high percentage of unknown primary melanoma (17%), at least partly representing completely regressed melanomas, indicates the importance of immune surveillance in melanoma progression.